Power-free contact lens for glucose sensing - Li, Zongkang (2023)
Recent advances in wearable devices have enabled noninvasive monitoring for healthcare applications. Smart contact lenses have gained substantial attention for medical diagnosis through the analysis of vital signs in tear fluids. However, previous studies have mostly focused on designs embedded with electronic devices or antennas for wireless transmission, which are power-intensive and require external receivers around the ocular system. Here, the study reports a power-free smart contact lens for noninvasive glucose sensing according to the color changes of multiple electrochromic electrodes to achieve direct data transmission without the external wireless system. The device detects various glucose concentrations, from the ordinary range (0.16–0.5 mm) to abnormally high concentrations (0.9 mm). The multi-electrode design exhibits acceptable accuracy, with a correlation coefficient r = 0.99543 to the controlled sample and allowed low-glucose detections with concentrations down to 0.05 mm. The device shows good reproducibility, with standard deviations of determined glucose levels of 0.0462 and 0.025 for four continuous cycles and for an interval of several days, respectively. It is believed that the reported smart contact lens has the potential for daily health monitoring by ordinary users without a power supply and external devices. Its simple electronics-free structure will allow for immediate application to the market with cost-effective manufacturing.